Adiabatic preparation of maximum entanglement in hybrid quantum systems with the Z2 symmetry. Issue 2 (12th May 2021) - Yang, Shuang‐Liang; Zhou, Yuan; Lü, Dong‐Yan; Ma, Ming; Wang, Qing‐Lan; Zhang, Xing‐Qiang
Abstract: A simple theoretical scheme with respect to preparing the maximum entanglement of a nitrogen‐vacancy (NV) spin and the quantized nanotubes carried with the tunable direct current is studied in this work. Basing on its inherent ℤ 2 symmetry of the general Jaynes–Cummings model in this spin–phonon coupling system, two special adiabatic channels to bridge the initial discrete ground states and the final ground states with the maximum entanglement are discussed. To further supplement this scheme, we also discuss another equivalent and suitable setup, namely the NV spin and surface acoustic wave strong strain coupling scheme. Owing to adiabaticity, this scheme may be considered as an encouraged attempt for preparing the nonclassical state utilizing the systemic symmetry.